Inline digital holographic movie based on a double-sideband filter - Ramirez, Claudio (2015)
This Letter proposes a new optical architecture based on a double-sideband filter, simultaneously applied at the Fourier plane, for inline digital holography. The proposed architecture not only allows removal of the conjugate images in the reconstruction process but also reduces the distortions that usually appear when using a single-sideband filter. We first introduce the mathematical model that explains the method and then describe the optical setup used for the implementation. The optical system includes a parallel aligned liquid crystal display placed at the Fourier plane that simultaneously filters positive and negative frequencies, when properly combined with linear polarizers. This feature makes the device useful to register dynamic processes. Finally, we tested the setup by registering a holographic movie of microscopic moving objects placed at different planes.